2010
DOI: 10.1016/j.bbabio.2010.02.020
|View full text |Cite
|
Sign up to set email alerts
|

Variable proton-pumping stoichiometry in structural variants of cytochrome c oxidase

Abstract: Cytochrome c oxidase is a multisubunit membrane-bound enzyme, which catalyzes oxidation of four molecules of cytochrome c2+ and reduction of molecular oxygen to water. The electrons are taken from one side of the membrane while the protons are taken from the other side. This topographical arrangement results in a charge separation that is equivalent to moving one positive charge across the membrane for each electron transferred to O2. In this reaction part of the free energy available from O2 reduction is cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
77
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(81 citation statements)
references
References 158 publications
4
77
0
Order By: Relevance
“…Proton transfer from the Glu to the catalytic site would take place only from one of these configurations. The observed apparent pK a would then reflect the equilibrium constant of the two configurations and their pK a values (50,52). Any changes in the observed pK a as a result of mutations-for example, around the 139 site-were explained in terms of changes in the energy profile for proton transfer through the D pathway and changes in the equilibrium constant for the two configurations of Glu-286.…”
Section: Discussionmentioning
confidence: 99%
“…Proton transfer from the Glu to the catalytic site would take place only from one of these configurations. The observed apparent pK a would then reflect the equilibrium constant of the two configurations and their pK a values (50,52). Any changes in the observed pK a as a result of mutations-for example, around the 139 site-were explained in terms of changes in the energy profile for proton transfer through the D pathway and changes in the equilibrium constant for the two configurations of Glu-286.…”
Section: Discussionmentioning
confidence: 99%
“…In these variants the lower stoichiometry could be explained in terms of a competition of proton transfers from a protonatable site (Glu286) within the D proton pathway to a pump site and the catalytic site, respectively (20). In this case the proton-pumping stoichiometry can adopt any value 0-1 depending on the relative rates of internal proton transfers to these two sites.…”
mentioning
confidence: 99%
“…When addressing this problem it is essential to investigate the individual electron-and proton-transfer reactions in the CytcOs (for review, see, e.g., ref. 20). In a representative experiment, all four electrons needed for reduction of O 2 to H 2 O are preloaded into the four redoxactive sites (Cu A , heme a∕b, heme a 3 , and Cu B ) of these enzymes in the absence of O 2 but in the presence of carbon monoxide, which binds to the reduced heme a 3 .…”
mentioning
confidence: 99%
“…1), is unknown. It is speculated that replacement with a charged residue, such as N139D, induces decoupling by shifting the pK a of the E286 via long-range electrostatic interactions (e.g., with the negatively charged D139 residue) (20,21). However, proton pumping can also be decoupled by the replacement of N139 with charge-neutral residues (e.g., N139T, N139C, and N139L), suggesting a more nuanced decoupling mechanism for these mutants.…”
mentioning
confidence: 99%
“…The decoupling mutants maintain the O 2 reduction reaction [often at the same rate as the wild-type (WT) CcO], but fail to couple the chemical reaction to proton pumping (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Mutagenesis studies have further revealed several residues in the D-channel that are essential for efficient proton pumping.…”
mentioning
confidence: 99%